A Rare Case of Adrenocortical Carcinoma Presenting as Cushing’s Syndrome - Nepal, R; Bisht, A; Shrestha, PS; Bajracharya, MR (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: We report a case of adrenocortical carcinoma presenting with atypical features of Cushing’s syndrome in a young 20 year old female with duration of symptomatology of four months. It is imperative to consider malignancy as differential diagnosis for etiology of Cushing’s syndrome with acute to subacute presentation.